Impacts of a Comprehensive School Readiness Curriculum for Preschool Children at Risk for Educational Difficulties. Issue 6 (28th October 2015) - Lonigan, Christopher J.; Phillips, Beth M.; Clancy, Jeanine L.; Landry, Susan H.; Swank, Paul R.; Assel, Michael; Taylor, Heather B.; Klein, Alice; Starkey, Prentice; Domitrovich, Celene E.; Eisenberg, Nancy; de Villiers, Jill; et al.
Abstract : This article reports findings from a cluster‐randomized study of an integrated literacy‐ and math‐focused preschool curriculum, comparing versions with and without an explicit socioemotional lesson component to a business‐as‐usual condition. Participants included 110 classroom teachers from randomized classrooms and approximately eight students from each classroom ( N  =   760) who averaged 4.48 ( SD  = 0.44) years of age at the start of the school year. There were positive impacts of the two versions of the curriculum on language, phonological awareness, math, and socioemotional outcomes, but there were no added benefits to academic or socioemotional outcomes for the children receiving explicit socioemotional instruction. Results are discussed with relevance to early childhood theory, policy, and goals of closing the school readiness gap.